New anti-HBV sesquiterpene glycosides and amino acid–sesquiterpene conjugates from the roots of Saussurea lappa. (February 2023) - Yang, Tianrong; Wu, Junqi; Wang, Yunfen; Yang, Kong; Cong, Xinyu; Chen, Hao; Li, Haizhou; Su, Lihua; Feng, Yang; Xu, Min
Abstract: Sesquiterpenes are modified triterpenes widely distributed in many plants and show potential biological activities. As part of an ongoing effort to search for comprehensive anti-HBV sesquiterpenes from herbs, herein we reported six new sesquiterpenes, saussunosids A-E (1, 3 −6 ) and saussureamine F (2 ), as well as three known sesquiterpenoids (7 −9 ) and one known acetylenic glucosides (10 ), from the roots of S. lappa collected in Lijiang county, Yunnan province, China. Saussunosids A-E (1, 3 −6 ) were new sesquiterpene glycosides and saussureamine F (2 ) was a new amino acid–sesquiterpene conjugate. Their structures were determined by extensive analyses of NMR, HR-ESI-MS and acid hydrolysis. The absolute configuration of the new compounds (1 −6 ) was established by coupling constants and ROESY correlations, as well as comparisons of the calculated ECD with the experimental ECD spectrum. Anti-hepatitis B virus (anti-HBV) activity evaluation suggested that compounds 2 and 7 showed inhibition of HBsAg with the value of 66.50% and 72.97%, respectively, while having no effects on HBeAg at 30 μM. Moreover, compounds 2 and 7 showed significant cytotoxicity with CC50 values of 14.85 ± 4.95 and 11.70 ± 2.04 μM against human hepatic cancer (HepG2), respectively. Graphical Abstract: ga1 Highlights: Six new sesquiterpenes were isolated and determinated from roots of S. lapp . The structures were elucidated by extensive spectroscopic data and acid hydrolysis. Saussureamine F (2 ) and saussureamine C (7 ) showed inhibition of HBV in HepG2.2.15. Saussureamine F (2 ) and saussureamine C (7 ) showed significant cytotoxicity in HepG2.